Kāvyāvalokanaṃ - Nāgavarma,Dēvīrappa, Ec. (Kannaḍa Sāhitya Pariṣattu, 2004)
On Kannada prosody and versification
Includes bibliographical references and index. - In Kannada; includes introd. in English. - Kannada in Kannada-Schr
Keywords: Kannada poetry; Kannada language